Spatiotemporal and direct capturing global substrates of lysine-modifying enzymes in living cells - Hao Hu; Wei Hu; An-Di Guo; Linhui Zhai; Song Ma; Hui-Jun Nie; Bin-Shan Zhou; Tianxian Liu; Xinglong Jia; Xing Liu; Xuebiao Yao; Minjia Tan; et al. (Nature Communications, 2024)
Abstract Protein-modifying enzymes regulate the dynamics of myriad post-translational modification (PTM) substrates. Precise characterization of enzyme-substrate associations is essential for the molecular basis of cellular function and phenotype. Methods for direct capturing global substrates of protein-modifying enzymes in living cells are with many challenges, and yet largely unexplored. Here, we report a strategy to directly capture substrates of lysine-modifying enzymes via PTM-acceptor residue crosslinking in living cells, enabling global profiling of substrates of PTM-enzymes and validation of PTM-sites in a straightforward manner. By integrating enzymatic PTM-mechanisms, and genetically encoding residue-selective photo-crosslinker into PTM-enzymes, our strategy expands the substrate profiles of both bacterial and mammalian lysine acylation enzymes, including bacterial lysine acylases PatZ, YiaC, LplA, TmcA, and YjaB, as well as mammalian acyltransferases GCN5 and Tip60, leading to discovery of distinct yet functionally important substrates and acylation sites. The concept of direct capturing substrates of PTM-enzymes via residue crosslinking may extend to the other types of amino acid residues beyond lysine, which has the potential to facilitate the investigation of diverse types of PTMs and substrate-enzyme interactive proteomics.